An Exploration of Students Mental Models on Heat and Temperature: A Preliminary Study - Rian Priyadi; Markus Diantoro; Parno Parno; Helmi Helmi (Jurnal Penelitian Fisika dan Aplikasinya (JPFA), 2019)
The mental models are internal representation possessed by students when learning a concept. This study is intended to explore students mental models on Heat and Temperature concept. This research was conducted on 11th grade students of Science program (N = 60) at one senior public school in Malang. Data were collected through open-ended questions and analyzed using the SSI method, which consisted of three levels of mental models. Based on the results, most of the students are still at the synthetic level. In addition, some differences of the students in visualizing the state of solid atoms during expansion, direction of heat conduction, and direction of heat convection. The future study is expected to explore the mental models of students in other topics of Physics education and make use of appropriate learning models to increase students mental models.